Business Plans From New Venture Perspectives: Enlightening or Destroying - Professor Dr Wan Sabri Wan Hussin (International Journal of Economics, Business and Innovation Research, 2022)
The dynamic, competitive and complex business environment nowadays demanded for entrepreneurs or new players in business venturing to create extra ordinary sustainable competitive advantages in order to achieve the business stated objectives, missions and vision simultaneously excel in the market. One of the well-known recipes and tools to achieve these dreams is through a well written and excellent business plan. Business planning is known as one of the business management tools used to achieve those stated venture’s dreams (objectives, missions and vision simultaneously excel in the market). Consequently, a business venture should prepare a convincing and promising business plan to attract investors. It is known that, investors are willing to invest or will be more prepared to invest in a business venture when they believe that the business planning is realistic and profitable based on their forecast and prediction of the business viability. When business plan is prepared based on correct information and data, investors will have confidence in the market, product or service of the business. The accuracy of a business plan will reflect the management’s ability, experience and history in running the business. Undeniable, many new ventures failed due to the failure of entrepreneurs to prepare an excellent business plan. Nevertheless, what it takes to develop a good business plan? Therefore, this paper will critically discuss the various aspects in the recipe of making a business plan an excellent document for new venture entrepreneurs. Careful analyses of twenty-one articles with different themes pertaining to business plan and its relationship to the success or failure of any new ventures yields some insights on issues prevalent in the matter. This paper may be useful for any new venture entrepreneurs as a guide for them as tools to clearly understand the concepts of business plans, the characteristics of an excellent business plan, the importance of business plans as well as the recipes to success which relating to the development of excellent business venture